Pengaruh Likuiditas, Perputaran Piutang, Pertumbuhan Volume Pinjaman, dan Modal Sendiri Terhadap Return on Assets - Anggraini, Dewi Ayu; Kusmuriyanto, Kusmuriyanto (Jurusan Pendidikan Ekonomi, Fakultas Ekonomi, Universitas Negeri Semarang, 2021)
This study aims to determine the effect of liquidity, accounts receivable turnover, loan volume growth and own capital on return on assets in KPRI, Rembang Regency partially or simultaneously. The sample in this study were 15 KPRI using purposive sampling technique. The data collection technique is documentation, namely in the form of the annual financial statements of cooperatives in 2016-2017. Data analysis techniques used descriptive statistics and multiple linear regression analysis. The results showed that partially there was a significant influence of receivables turnover on return on assets, there was a significant effect of own capital growth on return on assets. Meanwhile, liquidity and own capital have no significant effect on return on assets. However, simultaneously liquidity, receivables turnover, loan volume growth and own capital have an influence on return on assets.